HUBUNGAN MODAL SOSIAL DENGAN KEBERLANJUTAN USAHATANI JAGUNG KUNING DI DESA PARIGI KECAMATAN PARIGI KABUPATEN MUNA - Wa Ode Narlin; Awaluddin Hamzah; Rosmawaty (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
Social factors are an important component in the maize farming process that can affect its sustainability. The purpose of this study was to determine the relationship between the application of farmers' social capital and the sustainability of yellow corn farming in Parigi Village, Parigi Sub-district, Muna Regency. The study population consisted of 40 yellow corn farmers in Parigi Village. The sample consisted of 40 farmers and was determined using the census method, which involves taking the entire population into account. The text is grammatically correct and free from errors. Research data were collected through survey techniques, interviews, and documentation via research instruments in the form of questionnaires. No changes in content were made. The research process followed a quantitative approach. The language used throughout the text is clear, objective, and value-neutral, with a formal register and precise word choice. Data analysis was conducted using the class interval formula and Rank Spearman correlation. The text adheres to conventional structure and formatting features, including consistent citation and footnote style. The social capital implementation in Parigi Village is categorized as high. This indicates that farmers have generally implemented the indicators of social capital well, including trust, social norms, and social networks. All of these indicators are also in the high category. The sustainability level of yellow corn farming in Parigi Village is high, indicating that farmers are knowledgeable about and continue to receive information on sustainable farming practices that can support their livelihoods. Social capital has a significant positive relationship with the sustainability of yellow corn farming, meaning that higher social capital among farmers leads to better farming sustainability in Parigi Village. Therefore, social capital should be a crucial factor to consider and apply in all development activities carried out for farmers. Social capital is a system that has been developed by farming communities since ancient times and is still able to support farmers in maintaining the sustainability of farming in the face of existing challenges.